Perjalanan Pahlawan: 12 Tahapan dalam Narasi Film Animasi Boboiboy 2 - Oscar Gordon Wong; Imelda Ann Achin (Institut Seni Indonesia Denpasar, 2021)
2019 is a phenomenal year for the development of the Malaysian animated film industry as it has successfully produced two superheroes animated films in total. However, the animated film industry in Malaysia is still not competitive at the international level. This can be seen from the 17 animated films that have been produced from 1998 to 2019, only two superheroes animated films managed to get the attention of the audience. This is due to the lack of knowledge of the concept and function of the hero character in animated films. Therefore, the main objective of this paper aims to demonstrate how the Hero’s Journey narrative structure can be applied in BoBoiBoy Movie 2 (2019). This research method involves the use of video analysis tools namely Kinovea and Motion Picture Analysis Worksheet to explain on how the Hero’s Journey of this film conveys the storytelling. The results of this study found that each semicircle Hero’s narrative structure has an important meaning across from one half-circle to the other half-circle. As a result, it explains the concept of peace and chaos as well as stasis and changes in the narrative structure of superhero animated films. This paper will provide information to researchers on the importance and use of the Hero’s Journey approach to analyze superhero animated films.